Determinant Factors of Intention to Pay Zakat Profession Among Government Civil Servant - Zakaria Batubara; Faruq Baihaki Muhammad; Decky Hendarsyah; Ali Ambar; Akhmad Affandi Mahfudz (International Journal of Zakat, 2023)
Zakat collection in Indonesia remains sluggish growth compared to its potential of collection as majority of Indonesian population are Muslim. This study aims to analyze and show the influence of knowledge of zakat, religiosity, institutional image, and transparency towards the intention of government civil servant to pay zakat profession in Bengkalis town, Riau province, Indonesia. This study employs descriptive quantitative methods with primary and secondary data sources such as questionnaires and literature. The population of this study is all government civil servant registered in Bengkalis town in 2021 of 6,752 people. Sampling approach undertakes an incidental technique with sample measurements using the Yamane formula to obtain a sample of 378 people. The data analysis technique undergoes multiple linear regressions using SPSS software. The results of this study indicate that knowledge of zakat, religiosity, institutional image, and transparency positively and significantly affect the government civil servant’s intention to pay zakat profession. Religiosity is the dominant factor influencing the intention of government civil servant in paying zakat profession. This study complements the existing theory. Practically it can be used as reference material for zakat management institutions in increasing muzakki’s intention in paying zakat.